Text processing strategy instruction combined with bimodal bilingual inputs - Lee, Seung Chun (Routledge, 2015)
This study examines the combined effects of text processing strategy training and bimodal (listening and reading) bilingual (English and Korean) input conditions on the reading achievement of Korean learners of English. Learner training had two facets: one provided an explicit training of text processing strategies which facilitate building and activating learners’background knowledge, and the other gave optimal input conditions using two languages which help learners get automatic recognition of syntactic and semantic aspects of texts. Six groups of students each were assigned to one of the six input conditions combined with dual modes and bilingual processing. All of them had the same explicit strategy training, followed by text comprehension tests. The pre- and post-test measures showed that explicit strategy training enhanced the more proficient learners’ ability to comprehend English texts. One-way ANOVA indicated that the Bimodal D text (listening to L1 translations and reading L2 texts simultaneously) was the most effective bimodal aid to L2 text comprehension and L1 had a significantly facilitative effect on understanding of L2 text for any level of English learners. An interactive processing model of reading is proposed based on the results.